Comparative study between benzydamine hydrochloride gel, lidocaine 5% gel and lidocaine 10% spray on endotracheal tube cuff as regards postoperative sore throat - Nashwa Abdallah Mekhemar (Revista Brasileira de Anestesiologia, 2016)
ABSTRACT Postoperative sore throat is a common complication after endotracheal intubation. After tracheal intubation, the incidence of sore throat varies from 14.4% to 50%. The aim of the study was to compare between benzydamine hydrochloride gel, lidocaine 5% gel and lidocaine 10% spray on the endotracheal tube cuff as regards postoperative sore throat. The present study was carried out on 124 patients admitted to Alexandria university hospitals for lumbar fixation surgery requiring general anesthesia. Patients were randomly allocated into 4 groups. Benzydamine hydrochloride gel, 5% lidocaine hydrochloride gel, 10% lidocaine hydrochloride spray, or normal saline were applied on endotracheal tube cuffs before endotracheal intubation. The patients were examined for sore throat (none, mild, moderate, or severe) at 0, 1, 6, 12, and 24 h after extubation. The results were collected, analyzed and presented in table and figure. The highest incidence of postoperative sore throat occurred at 6 h after extubation in all groups. There was a significantly lower incidence of postoperative sore throat in the benzydamine group than 5% lidocaine gel, 10% lidocaine spray, and normal saline groups. The benzydamine group had significantly decreased severity of postoperative sore throat compared with the 10% lidocaine, 5% lidocaine, and normal saline groups at observation time point. Compared with the 5% lidocaine the 10% lidocaine group had significantly increased incidence and severity of postoperative sore throat after extubation. Compared with normal saline the 10% lidocaine group had increased incidence of postoperative sore throat. There were no significant differences among groups in local or systemic side effects. So in conclusion, benzydamine hydrochloride gel on the endotracheal tube cuff is a simple and effective method to reduce the incidence and severity of postoperative sore throat. Application of 10% lidocaine spray should be avoided because of worsening of postoperative sore throat where incidence increased but not the severity in relation to 5% lidocaine gel. Applying 5% lidocaine on the endotracheal tube cuff does not prevent postoperative sore throat but its application is better than lidocaine 10% spray or saline.